Acoustic quantification indexes of left ventricular size and function: effects of signal averaging. - Mor-Avi, V; Vignon, P; Bales, A C; Spencer, K T; Lang, R M (Journal of the American Society of Echocardiography, 1998)
Background: The aim of this study was to evaluate the clinical utility of using signal-averaged acoustic quantification (SAAQ) waveforms for improved assessment of left ventricular (LV) size and function.Methods and Results: Four separate protocols were performed in 47 subjects. SAAQ waveforms were used to assess alterations in LV function induced by dobutamine (15 microg/kg per minute) and esmolol (200 microg/kg per minute) in eight normal subjects. Subsequently, we analyzed SAAQ waveforms obtained in 12 patients with LV dysfunction secondary to dilated cardiomyopathy and 12 age-matched normal subjects. Finally, we developed computer software for monitoring of LV function on the basis of continuous acquisition and repeated analysis of SAAQ waveforms. We compared the interbeat variability in indexes of LV function obtained from raw AQ and SAAQ during 10 minutes of steady-state monitoring in eight patients undergoing transesophageal echocardiography. The feasibility of long-term monitoring in the intensive care setting was then studied in seven patients undergoing abdominal surgery. Our analysis tracked variations in LV function induced by dobutamine and esmolol. Significant differences in all measured indexes were found between normal subjects and patients with dilated cadiomyopathy. Signal averaging during steady-state monitoring significantly reduced the interbeat variability of all indexes (21% to 42%). In the operating room, the SAAQ monitoring system tracked hemodynamic changes in close agreement with invasive measurements.Conclusions: SAAQ allows fast and easy quantification of LV function and can track hemodynamic trends in the operating room setting.